Development and characterization of swiftlet nest-based formulation in nano-cosmeceuticals - Mohd Taib, Siti Husnaa (2015)
Purified swiftlet nest (SN) was used as an active ingredient in the development of nano-cosmeceuticals using homogenizer. The sample preparation method comprises cleaning, drying with freeze dryer and grinding of SN. Then the fine powder of SN was added to the formulation. Prior to addition of SN into the formulation, the compound present in raw SN and purified SN were identified and compared by Fourier Transform Infrared (FTIR) spectroscopy analysis, nitrite test, protein analysis and moisture analysis. One of the major nutrients in SN is protein. The protein content in purified SN (60.1%) higher than raw SN (57.5%) which is differs significantly at 95% confidence level. This was due to “Freeze-Drying" method that was carried out by low operating temperature. This process leads to minimal damage of the heat-sensitive materials. Hence, protein is able to be preserved and enhanced. The study showed raw SN has low concentration of nitrite (0.25 ppm) whereas purified SN devoid of nitrite. Making frequent water changes during the process of cleaning SN was able to reduce nitrite as nitrite is highly soluble in water. The FTIR results indicated that the main compounds present in the SN samples were carbohydrates and protein. Moisture content of purify SN should be less than 10%. For this study, moisture content of the purified SN (7.45%) was slightly higher from its raw SN (5.62%). The formulations consisted of oil in water emulsions. In manufacturing cosmetics,formulation and optimization processes are two important issues. In this work, Response surface methodology (RSM) was utilised in order to investigate the influence of the nano-cosmeceuticals composition; purified SN (1–5% w/w), and Tween 80 (3- 6% w/w) as well as the preparation method; time of homogenization (10–30 min), on the physicochemical properties of swiftlet nest-based nano-cosmeceuticals. The response variables were particle size and zeta potential which are very important characteristic in nano-cosmeceuticals. Formulation and optimization of three independent variables were carried out to obtain an optimum SN-based nanocosmeceutical with the lowest particle size and high stability formulation. After the optimization process, formulation coded as SN25 was selected as the best formulation with the particle size of 136.35 nm and zeta potential of -40.2 mV. This was obtained experimentally and was closer to the predicted value 136.22 nm and - 40.07 mV, respectively. Formulation SN25 was determined to be 2.58% SN, 3.99% Tween 80, 90.03% deionized water and 3.4% other ingredients, with a time of homogenization of 17 min. The pH value of optimized formulation was 6.49. The formulation was stable after undergoing thaw cycles test, at room temperature and 45°C for three months. The rheological property of optimized formulation was investigated using rheometer. The viscosity of the optimized formulation was found to decrease with the increase in the applied shear rate. Thus, these types of formulation could be categorized as pseudoplastic or shear thinning material. The optimized formulation was found to be non-irritating with a Human Irritancy Equivalent (HIE) score below 0.90. Potassium sorbate used as preservative in the formulations successfully prevented microbial growth. The inhibition zone activities of formulation showed inhibitions bacteria Methicillin Resistant Staphylococcus aureus (MRSA) and yeast Candida albicans.